Cost Variation Analysis of Corticosteroids Available in India: An Observational Study - Dr. Ramya Rachamanti; Dr. Supriya Sanke; Dr Ch. Jhansi Vani; Dr Rajesh Dupaguntla (International Journal of Pharma and Bio Sciences, 2023)
Pharmacoeconomics refers to the scientific discipline that compares the value of one pharmaceutical drug or drug therapy to another. Cost variation analysis on various brands of corticosteroids available in the Indian market provides information on price differences between these brands. It can decrease the price fluctuations in the market. The novelty of the current study is that it could help frame guidelines regarding price capping for various drug companies. The current study assessed cost variation analysis among all corticosteroid brands available in India. The objectives include assessment of the dose, no. of brands available, minimum and maximum price, cost ratio, percentage cost variation, and mean price of each medication. This study used the Drug Today book dated Jan 2022(DT 114), published annually. The study was done in the Department of Pharmacology at a tertiary care center named Government Medical College, Ongole, Andhra Pradesh, India. The study was done for 1 week during March 2023. All corticosteroid brands mentioned in Drug Today book, including topical, inhalational, oral, and parenteral dosage forms, both monotherapy and combination therapies, were included. Results showed a significant difference in the mean price of various oral and parenteral corticosteroid brands available in India. Price variation is maximum for prednisolone among oral preparations and triamcinolone among parenteral preparations. Our study concludes that a huge variation in pricing is seen in the Indian context for various corticosteroids. Physicians should also be made aware of the prices of various medications while encouraging them to prescribe generic medicines. It suggests that prescribing drugs in generic names will allow the pharmacist to dispense suitable and cost effective drugs to the patient.